Why Shouldn't We Feed Water Birds? - Mark E. Hostetler; Martin B. Main; Maena Voigt (EDIS)
"Water birds" are birds that live in or near aquatic environments such as the ocean, lakes, marshes, swamps, and rivers. This includes pelicans, ducks, geese, herons, egrets, gulls, terns, cormorants, etc. Feeding water birds leads to many different problems. This document is Fact Sheet WEC 179, one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published November 2003.